VALIDITAS DAN RELIABILITAS TES DISPOSISI BERPIKIR KRITIS DALAM BIOLOGI PERGURUAN TINGGI - Jayanti Syahfitri; Harry Firman; Sri Redjeki; Siti Sriyati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The purpose of this study was to look at the content validity and reliability of Critical Thinking Disposition Tests (CTDT). The CTDT consists of 10 groups of questions, each of which consists of 7 questions that lead to CTD. This research was conducted at two Universities in Bengkulu involving biological education students. The total number of respondents is 526 students taken from the level of study, namely the 1st, 2nd, 3rd and 4th year. After being validated by some experts the results show that content validity of CTDT has valid. In addition reliability test results show that CTDT overall has a high reliability of 0.978. While, the reliability value is based on Composite Reliability (CR) and Cronbach Alpha for each indicator in sequence, truth seeking (CR = 0.96 and Cronbach = 0.962), open mind (CR = 0.94 and Cronbach = 0.937), analicity ( CR = 0.97 and Cronbach = 0.969), sistematicity (CR = 0.96 and Cronbach = 0.957), self confidence (CR = 0.98 and Cronbach = 0.979), inquisitiveness (CR = 0.93 and Cronbach = 0.926) and maturity (CR = 0.97 and Cronbach = 0.967).The best score for disposition is on open mind and most students have an ambivalent. Keywords: validitas, reliabilitas, disposisi berpikir kritis